Supervised Cycling Training Improves Erythrocyte Rheology in Individuals With Peripheral Arterial Disease - Hsu, Chih-Chin; Lin, Yu-Ting; Fu, Tieh-Cheng; Huang, Shu-Chun; Lin, Cheng-Hsien; Wang, Jong-Shyan (Frontiers in Physiology, 2022)
Peripheral arterial disease (PAD) results in insufficient flow to lower extremities. Aerobic exercise provides health benefits for individuals with PAD, but basic science behind it is still debated. Twenty-one PAD patients aged about 70 years with female/male as 7/14 were recruited. Among them, 11 were randomized to have supervised cycling training (SCT) and 10 to receive general healthcare (GHC) as controls. SCT participants completed 36 sessions of SCT at the first ventilation threshold within 12 weeks and the controls received GHC for 12 weeks. Ankle-brachial index (ABI), 6-min walk test (6MWT), peak oxygen consumption (V˙O2peak), minute ventilation (V˙E), minute carbon dioxide production (V˙CO2), erythrocyte rheology, including the maximal elongation index (EImax) and shear stress at 50% of maximal elongation (SS1/2), and the Short Form-36 (SF-36) questionnaire for quality of life (QoL) were assessed before and 12 weeks after initial visit. SCT significantly decreased the SS1/2 as well as SS1/2 to EImax ratio (SS1/2/EImax) and increased the erythrocyte osmolality in the hypertonic region as well as the area under EI-osmolality curve. The supervised exercise-induced improvement of erythrocyte deformability could contribute to the increased peripheral tissue O2 delivery and was possibly related with increased V˙O2peak. The physiological benefit was associated with significantly increased ABI, 6-min walking distance, cardiorespiratory fitness, and SF-36 score. However, no significant changes in aerobic capacity and erythrocyte rheological properties were observed after 12-week of GHC. In conclusion, SCT improves aerobic capacity by enhancing erythrocyte membrane deformability and consequently promotes QoL in PAD patients.